Alkaline-Earth Metal Mediated Benzene-to-Biphenyl Coupling - Mai, Jonathan; Morasch, Michael; Jedrzkiewicz, Dawid; Langer, Jens; Rösch, Bastian; Harder, Sjoerd (Angewandte Chemie International Edition, 2022)
Complex [(DIPePBDI)Ca]2(C6H6), with a C6H62− dianion bridging two Ca2+ ions, reacts with benzene to yield [(DIPePBDI)Ca]2(biphenyl) with a bridging biphenyl2− dianion (DIPePBDI=HC[C(Me)N-DIPeP]2; DIPeP=2,6-CH(Et)2-phenyl). The biphenyl complex was also prepared by reacting [(DIPePBDI)Ca]2(C6H6) with biphenyl or by reduction of [(DIPePBDI)CaI]2 with KC8 in presence of biphenyl. Benzene-benzene coupling was also observed when the deep purple product of ball-milling [(DIPPBDI)CaI(THF)]2 with K/KI was extracted with benzene (DIPP=2,6-CH(Me)2-phenyl) giving crystalline [(DIPPBDI)Ca(THF)]2(biphenyl) (52 % yield). Reduction of [(DIPePBDI)SrI]2 with KC8 gave highly labile [(DIPePBDI)Sr]2(C6H6) as a black powder (61 % yield) which reacts rapidly and selectively with benzene to [(DIPePBDI)Sr]2(biphenyl). DFT calculations show that the most likely route for biphenyl formation is a pathway in which the C6H62− dianion attacks neutral benzene. This is facilitated by metal-benzene coordination.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Alkaline-Earth Metal; Cross-Coupling; DFT Calculations; Low-Valent; Mechanochemistry